Restri????o ao uso de subst??ncias perigosas (RoHS) no segmento de computadores pessoais: an??lise da estrat??gia de ado????o pelos fabricantes estabelecidos no Brasil - Brescansin, Ademir (2014)
The publication of the Restriction of Hazardous Substances (RoHS) directive in Europe, in 2003, limiting the use of the hazardous substances (lead, mercury, cadmium, hexavalent chromium and flame retardants based on bromine) has forced companies to adequate their products and process to comply with the legislation. Since then, many manufacturers of electrical and electronics equipment have adopted RoHS requirements for all of their products. Even in the absence of a similar legislation to RoHS in Brazil, it was noticed that manufacturers of personal computers settled in the country have adopted RoHS for products to be marketed in domestic market and abroad. The purpose of this study is to analyze if these manufacturers have adopted RoHS requirements focusing on their motivations, concerns and benefits in this regard. This is an exploratory research based on the literature and documental review and interviews. The interviews were carried out with professionals from eight companies associated to Brazilian Association of Electrical and Electronics Industry (ABINEE): Hewlett-Packard (HP), Dell, Sony, Lenovo, Samsung, LG, Itautec and Positivo. Content analysis was the method used for analyzing the information gathered in the interviews. The results obtained showed that the multinational companies have adopted RoHS as a requirement to export to Europe and, later on, they expanded this adoption to 100% of the products, independently of the manufacturing or market country, including their suppliers and commercial partners. Brazilian companies, however, have adopted RoHS as a way to participate in the bidding of sustainable purchasing of Brazilian government. Therefore, it was observed that the adoption of RoHS in the manufacturing of personal computers in Brazil have resulted in the demand of exportation (force of law) and domestic markets (government bidding). In practical terms, it is expected, the results and reflections in this study can assist manufacturers of computers and other electronic equipment in developing their business strategies for RoHS adoption, providing competitive advantages and the benefits to the environment and people. It is also expected, assist the government in the formulation of policies regarding to restriction of the use of hazardous substances in all products sold in Brazil, reducing environmental contamination risks and allowing a better life quality for all people. It is recommended further studies, quantitative in nature, that could evaluate the cost of RoHS adoption, the impacts on the supply chain and possible implications in the costs of the products for end consumers.